Analysis of the Availability of Medical Laboratory Technology Experts (ATLM) Based on the Minimum Energy Standard of Permenkes No. 43 of 2019 in Indonesia Year 2023 - Rosmalinda; Dumilah Ayuningtyas (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Medical Laboratory Technology Experts (ATLM) as one type of health worker, are authorized to organize or practice in the health sector according to their expertise. The ideal ratio of Community Health Centers (Puskesmas) to districts is at least 1 Puskesmas per sub-district, and the minimum staffing standard based on Minister of Health Regulation No. 43 of 2019 for ATLM personnel in Puskesmas is 1 (one), both in Urban, Rural, Remote, and Very Remote Puskesmas. Method: The purpose of this study is to analyze the suitability of ATLM personnel with minimum staffing standards based on the Minister of Health Regulation No. 43 of 2019 in Indonesia. The qualitative research method describes the availability of ATLM personnel at the district/city/provincial level in Indonesia, using secondary data from the Ministry of Health's Health Human Resources Information System (SISDMK) for 2022. Result: The results showed that there is still a shortage of medical laboratory technologists in Puskesmas at the district/city/provincial level in Indonesia, with 1,486 Puskesmas experiencing a shortage out of a total of 10,436 Puskesmas in Indonesia.